2017
DOI: 10.1037/hea0000475
|View full text |Cite
|
Sign up to set email alerts
|

Does personality predict health and well-being? A metasynthesis.

Abstract: This metasynthesis provides among the most compelling evidence to date that personality predicts overall health and well-being. In addition, it may inform research on the mechanisms by which personality impacts health as well as research on the structure of personality. (PsycINFO Database Record

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

38
250
3
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 354 publications
(298 citation statements)
references
References 58 publications
(108 reference statements)
38
250
3
7
Order By: Relevance
“…However, there is now mostly agreement that individual differences in personality are associated with behaviours in other contexts (for impressive recent studies, see [46,47]). There is also considerable evidence that individual differences in personality are associated with later-life outcomes, such as relationship stability, success in school and work, socioeconomic status, happiness, mental and physical health, and length of life [48][49][50][51].…”
Section: The Two Disciplines Of Animal Personality Researchmentioning
confidence: 99%
“…However, there is now mostly agreement that individual differences in personality are associated with behaviours in other contexts (for impressive recent studies, see [46,47]). There is also considerable evidence that individual differences in personality are associated with later-life outcomes, such as relationship stability, success in school and work, socioeconomic status, happiness, mental and physical health, and length of life [48][49][50][51].…”
Section: The Two Disciplines Of Animal Personality Researchmentioning
confidence: 99%
“…Allen et al (2016) found that the link between neuroticism and sleep difficulties is mediated by its association with the tendency to experience more negative affect, whereas extraversion is associated with better sleep quality through its link with more positive affect. Moreover, neuroticism is related to higher stress sensitivity (Friedman & Kern, 2014; Leger, Charles, Turiano, & D’Almeida, in press), and worse mental and physical health (Strickhouser, Zell, & Krizan, in press; Sutin et al, 2013), which can disrupt sleep quality. Extraverted and conscientious individuals have better mental and physical health (Strickhouser et al, in press), and lower reactivity to stressors (Leger et al, in press), which may lead to better sleep quality.…”
mentioning
confidence: 99%
“…Moreover, neuroticism is related to higher stress sensitivity (Friedman & Kern, 2014; Leger, Charles, Turiano, & D’Almeida, in press), and worse mental and physical health (Strickhouser, Zell, & Krizan, in press; Sutin et al, 2013), which can disrupt sleep quality. Extraverted and conscientious individuals have better mental and physical health (Strickhouser et al, in press), and lower reactivity to stressors (Leger et al, in press), which may lead to better sleep quality. In addition, higher neuroticism and lower conscientiousness are related to health-related behaviors that can undermine sleep quality, such as physical inactivity, smoking, and alcohol consumption (Hakulinen et al, 2015a, 2015b; Sutin et al, 2016).…”
mentioning
confidence: 99%
“…To explain why certain people are healthier than others, a wide variety of personality concepts and their relationships with health outcomes have been studied. A recent metasynthesis provides some of the most compelling evidence to date that personality predicts overall health and well‐being (Strickhouser, Zell, & Krizan, 2017). University students, in particular, are frequently exposed to unhealthy behaviors and exhibit low HPB, and Type D personality has been reported to associate with health behaviors, health status, and QoL (Gilmour & Williams, 2012; Mols & Denollet, 2010; Williams & Wingate, 2012; Williams et al, 2016).…”
Section: Discussionmentioning
confidence: 99%